Pseudoxanthoma elasticum-associated angioid streaks near a scleral buckle - Karen E. Lee; Tobin B.T. Thuma; Mirataollah Salabati; Meera D. Sivalingam; Jose S Pulido; Kammi B. Gunton (American Journal of Ophthalmology Case Reports, 2024)
Purpose: We report a patient with pseudoxanthoma elasticum (PXE) with angioid streaks near a scleral buckle site. Observations: A 46-year-old male with PXE presented for evaluation of blurry vision and was found to have classic PXE findings in both eyes and angioid streaks adjacent to the site of a scleral buckle in his left eye. He underwent multimodal imaging, genetic testing, and intravitreal aflibercept in the right eye. Conclusions and importance: Bruch's membrane is known to be fragile in PXE, and patients are often counseled about the heightened risk of playing contact sports. This report raises the question of whether tension from a scleral buckle in the setting of a calcified and brittle BM may increase the likelihood of angioid streaks near the buckle site. In the setting of retinal detachment, it may be worthwhile to carefully weigh the pros and cons of vitrectomy versus buckle for PXE patients.